Childhood cancer burden and health inequality: A systematic analysis from the global burden of diseases study 2021 - Guotian Pei; Yingshun Yang; Shuai Wang; Shushi Meng; Jun Liu; Yuqing Huang (PLoS ONE, 2026)
Objective To estimate the burden, trends, and inequalities of childhood cancers (aged 0–14 years) at global, regional, and national levels from 1990 to 2021. Methods We analyzed Global Burden of Diseases Study (GBD) 2021 data, using age-standardized disability-adjusted life years (DALYs) rates (ASDR) to assess childhood cancer burden across 204 countries and territories, grouped into 21 GBD regions by the socio-demographic index (SDI). Temporal trends were assessed using Joinpoint regression. The slope index of inequality and concentration index were calculated to quantify absolute and relative inequalities in the disease burden. Results In 2021, childhood cancer caused 70.45 million (95% uncertainty interval [UI]: 57.7–82.79) DALYs globally, with 98.6% attributed to years of life lost. Global ASDR declined from 664.31 (95% UI: 552.99–785.90) in 1990 to 354.06 (95% UI: 289.08–417.49) per 100,000 in 2021. Low-SDI countries had the highest ASDR (467.41, 95% UI: 342.00–589.20), reflecting challenges in diagnosis, treatment, and healthcare access. Acute lymphoblastic leukemia dominated the burden in children under 5, while brain cancers were more common in the 10−14 age group. Boys exhibited higher ASDR (395.55, 95% UI: 307.57–477.68) versus girls (309.80, 95% UI: 253.75–364.91). Socioeconomic inequalities widened, with DALYs concentration index shifting from −0.03 (95% CI: −0.06–0.01) in 1990 to −0.13 (95% CI: −0.16 - −0.11) in 2021, reflecting disproportionate burdens in low-SDI countries. Conclusions Persistent disparities in childhood cancer outcomes highlight systemic inequities in healthcare access. High-SDI countries achieved significant mortality reductions, while low-SDI countries face escalating burdens due to delayed diagnoses and fragmented care. Prioritizing cost-effective innovations, strengthening healthcare infrastructure, and implementing gender-sensitive policies are critical to achieving Sustainable Development Goals 3.4 targets. Global collaboration to expand cancer registries and equitable resource allocation is urgently needed to mitigate disparities.